Autism impairs face perception? Opposite associations between different subclusters of autistic traits and illusory face detection - Wang, Keyu; Zhou, Liu-Fang; Ruan, Yonghua; Shi, Xinyu; Wen, Xiyun; Meng, Ming (Visual cognition, 2023)
Despite common beliefs about facial processing deficits in autism, many studies have failed to confirm qualitative impairments. Individual differences within the autistic population are likely key confounding factors. The dichotomy of the Autism Spectrum Quotient (AQ) has been recognized in psychometric literature among subclinical and clinical population, enabling large-sample research on how heterogeneous autistic traits affect face perception. Here we innovatively used face pareidolia, the illusion of seeing faces in non-face objects, to investigate how different autistic traits affect face perception. Our results showed that higher AQ-social scores (social and communication aspects) were linked to a lower likelihood of seeing illusory faces, while higher AQ-attention-to-detail scores (rigidity and pattern aspects) increased susceptibility to face pareidolia. A mediation model revealed that imagination mediates the relationship between autistic traits and face perception, suggesting diverse mechanisms in autism's impact on face-related processes.